The Y-chromosome - Jobling, Mark (Henry Stewart Talks, 2009)
Role in sex determination, Recombination behaviour, Sex-chromosomal aneuploidies, Type and number of genes, Rates and types of mutation, Associated diseases, Sequence organization, Diversity of Y chromosome types in populations